Risk Factors of the Bladder Cancer - Joanna Miśkiewicz; Aleksandra Sadowska; Aleksandra Welkier; Adam Sobiński; Aleksandra Dudek; Patrycja Pietrusińska; Jakub Moder; Anna Dziewierz; Paula Kwaśniewska; Patrycja Śliwa-Tytko (Quality in Sport)
Introduction and purpose: Bladder cancer [BC] is one of the most common cancers in the world. The number of cases of BC recorded in the National Cancer Registry has been approximately 7.5 thousand annually since 2013. The National Cancer Registry's "Cancer in Poland in 2021" report ranks BC as the 4 most frequent cancer in men in Poland. A deeper comprehension of the disease will aid in the creation of more effective preventative and therapeutic measures. Our effort aims to categorize and characterize risk factors [RF] for BC.